A collaborative approach to developing sustainable behaviour change interventions for childhood obesity prevention: Development of the Choosing Healthy Eating for Infant Health (CHErIsH) intervention and implementation strategy. Issue 2 (30th January 2020) - Toomey, Elaine; Matvienko‐Sikar, Karen; Doherty, Edel; Harrington, Janas; Hayes, Catherine B.; Heary, Caroline; Hennessy, Marita; Kelly, Colette; McHugh, Sheena; McSharry, Jenny; O'Halloran, Joanne; Queally, Michelle; et al.
Abstract : Objectives and Design: There is growing recognition of the need for effective behaviour change interventions to prevent chronic diseases that are feasible and sustainable and can be implemented within routine health care systems. Focusing on implementation from the outset of intervention development, and incorporating multiple stakeholder perspectives to achieve this, is therefore essential. This study explores the development of the Choosing Healthy Eating for Infant Health (CHErIsH) childhood obesity prevention intervention and implementation strategy to improve infant feeding behaviours. Methods: Five qualitative and quantitative evidence syntheses, two primary qualitative studies, and formal/informal consultations were conducted with practice, policy, research, and parent stakeholders. The Behaviour Change Wheel was used to guide the integration of findings. Results: The CHErIsH intervention targets parent‐level behaviour change and comprises (1) brief verbal messages and (2) trustworthy resources, to be delivered by health care professionals (HCPs) during routine infant vaccination visits. The implementation strategy targets HCP‐level behaviour change and comprises (1) a local opinion leader, (2) incentivized training, (3) HCP resources and educational materials, (4) electronic delivery prompts, (5) awareness‐raising across all primary care HCPs, and (6) local technical support. Conclusions: This study provides a rigorous example of the development of an evidence‐based intervention aimed at improving parental infant feeding behaviours, alongside an evidence‐based behaviour change strategy to facilitate implementation and sustainability in primary care. This approach demonstrates how to systematically incorporate multiple stakeholder perspectives with existing literature and move from multiple evidence sources to clearly specified intervention components for both the intervention and implementation strategy. Statement of Contribution: What is already known? Incorporating insights from practice, policy, and public/patient stakeholders plays a key role in developing behaviour change interventions that are feasible and sustainable and can be implemented within routine health care systems. However, there are limited examples that provide in‐depth guidance of how to do this using a systematic approach. What this study adds? This study describes an innovative use of the Behaviour Change Wheel to integrate multiple sources of evidence collected from practice, policy, research, and parent stakeholders to concurrently develop an evidence‐based intervention to improve parental infant feeding behaviours and an implementation strategy to facilitate sustainable delivery by health care professionals in routine primary care